A critical assessment of a landmark study. Issue 3 (3rd July 2017) - Dwork, Debórah
ABSTRACT: This article critically assesses a landmark study undertaken by the UCL Centre for Holocaust Education, What Do Students Know and Understand about the Holocaust? Analyzing the wealth of information offered by the study, the author widens the lens to contextualize the importance of this empirical research. At the same time, she critiques the gendered foci of the study design and suggests other fruitful perspectives. And she argues that this study is a key first step, with the results showing a clear path forward.